Kinerja Karyawan Ditinjau dari Pelatihan, Komunikasi dan Reward Studi pada PT. Pabrik Gula Mojo Kabupaten Sragen - Wahyu Prabowo Mukti; Supawi Pawenang; Raisa A. Hamidah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
An investigation of the performance of workers at PT. Mojo Sugar Factory in Sragen Regency is being carried out with the purpose of determining and explaining employee performance in relation to training, communication, and reward. A quantitative descriptive research design is something that is utilized in this research strategy. All of the workers that are employed in the PT Mojo Sugar Factory in the Sragen Regency make up the population for this research. A saturation sampling strategy, This research used what is commonly referred to as the census approach. A sample of the entire population is taken using this process. In this study, 102 workers were chosen as samples. A questionnaire was employed to gather data. Data analysis was done using statistical analysis, most especially using SPSS version 25 using the multiple linear regression test, the t test, and the coefficient of determination. The study's conclusions show that working personnel at PT. Mojo Sugar Factory perform better and more significantly when they receive training, which is located in the Sragen Regency. There is a favorable and considerable impact that communication has on the performance of employees at PT. Mojo Sugar Factory, which is located in the Sragen Regency. At PT. Mojo Sugar Factory, Sragen Regency, the performance of employees is significantly improved by the presence of rewards, which have a beneficial impact. When all factors are included, the coefficient of determination (R2) accounts for 53.5% of the total, while the remaining 46.5% is impacted by additional variables that were not investigated in this study.